Synthesis and characterization of castor oil-segmented thermoplastic polyurethane with controlled mechanical properties. (August 2016) - Nguyen Dang, Luong; Le Hoang, Sinh; Malin, Minna; Weisser, Jürgen; Walter, Torsten; Schnabelrauch, Matthias; Seppälä, Jukka
Graphical abstract: Highlights: A series of castor oil-segmented thermoplastic polyurethanes is developed. The polyurethanes show good mechanical properties and high optical transparency. Good cytocompatibility of the polyurethane is evaluated. Abstract: Novel castor oil-segmented thermoplastic polyurethane series (PUs) have been prepared and extensively characterized in this study. The castor oil, poly(tetrahydrofuran) polyol, and poly(dimethylsiloxane) have been employed as soft segments in the polymer synthesis with a maximum bio-based content up to 14.1 wt%. We demonstrate here that it is possible to prepare thermoplastic polyurethane containing castor oil via polyaddition approach in which the formation of prepolymer needs to be carried out with the addition of reasonably small amount of castor oil together with excess amount of the diisocyanate in the very first step. This is followed by the addition of the other polyols and finally a low molecular weight chain extender. The developed synthesis resulted in the formation of branched thermoplastic polyurethane with an elongation at break of about 1200%, which is considerably high compared to reported values for polyurethanes containing castor oil as soft segments. We have demonstrated that mechanical properties and flexibility of polyurethane can be significantly altered by both incorporated castor oil and controllable poly(dimethylsiloxane)/poly(tetrahydrofuran) polyol ratio during the synthesis. Especially the synthesized polyurethanes exhibited good biocompatibility and high transparency, which are useful properties for polymers as potential biomaterials. In addition, thermal stability and thermal transition of polyurethanes have been investigated.